2022
DOI: 10.3329/bjagri.v47i1.60593
|View full text |Cite
|
Sign up to set email alerts
|

Study on in vitro micropropagation of Rosa sp.

Abstract: Tissue culture has long been recognized as an ideal experimental paradigm for studying the mechanisms governing plant cell growth, division, and physiological and biochemical processes. The present investigation was undertaken to establish a standard method for callus induction, shoot and root regeneration of rose at Genetic Engineering and Biotechnology Laboratory, University of Rajshahi, Bangladesh in 2010. Shoot tip and nodal segments were used as experimental materials excised from field grown plants for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The medium containing only 3.0 mg/l BAP resulted in the highest percentage of responding callus (93.33 %) out of all the different concentrations and combinations tested, with an average 6.40 ± 0.51 shoots per culture and an average of 5.48 ± 0.36 cm shoot length. Similarly, Afrin et al (2022) and Liu et al (2018) also demonstrated that BAP was crucial for the development of adventitious buds from callus in different species of Rosa. When BAP concentrations were raised or lowered after 3.0 mg/l, responsive callus was also generated, but the number of shoots/culture and their length were also reduced.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The medium containing only 3.0 mg/l BAP resulted in the highest percentage of responding callus (93.33 %) out of all the different concentrations and combinations tested, with an average 6.40 ± 0.51 shoots per culture and an average of 5.48 ± 0.36 cm shoot length. Similarly, Afrin et al (2022) and Liu et al (2018) also demonstrated that BAP was crucial for the development of adventitious buds from callus in different species of Rosa. When BAP concentrations were raised or lowered after 3.0 mg/l, responsive callus was also generated, but the number of shoots/culture and their length were also reduced.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, the nature of callus obtained from different sources differed as well, as seen in Table 2. It was supported by the work of Harmon et al (2022) in the case of three different cultivars of R. hybrida; Afrin et al (2022) in the case of Rosa sp. ; Pourhosseini et al (2013) in the case of R. hybrida cv.…”
Section: Resultsmentioning
confidence: 93%